2021
DOI: 10.1002/er.6420
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the oxygen reduction reaction on Ni‐N‐C and Co‐N‐C catalysts derived from ZIF ‐8

Abstract: With industrial development and environmental deterioration, fuel cell catalysts have attracted the attention of scientists. Traditional platinum-based catalysts have been unable to meet research and commercial needs due to their expensive and unstable characteristics; so, it is necessary to find a replacement for platinum-based catalysts. Metal-nitrogen-carbon catalysts have gradually become popular due to their low cost and easy availability. In this paper, we designed 15 catalysts through ZIF-8 and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, this site is active enough to serve as the most suitable adsorption site. 39,40 The values of the Fukui function analysis of each Fe atom on Fe n -C 2 N (n = 2-4) are remarked in Fig. 5 and the position with the largest index is taken as the best adsorption site.…”
Section: Adsorption Of Reaction Speciesmentioning
confidence: 99%
“…Therefore, this site is active enough to serve as the most suitable adsorption site. 39,40 The values of the Fukui function analysis of each Fe atom on Fe n -C 2 N (n = 2-4) are remarked in Fig. 5 and the position with the largest index is taken as the best adsorption site.…”
Section: Adsorption Of Reaction Speciesmentioning
confidence: 99%
“…The center metal atoms play a major catalytic role by interacting directly with the intermediate molecule of ORR. Consequently, tuning the center metal atoms will significantly influence the intrinsic electrocatalytic activity of M-N-C. [97,98] For the strong electronic interactions between the coordinated atoms and the center metal atoms, the intrinsic activity will also be regulated by adjusting these coordinated atoms. Heteroatoms like S and P, which are known as environmental atoms, can be facilely doped into the carbon matrixes.…”
Section: Improving the Intrinsic Activity Of M-n 4 Sitesmentioning
confidence: 99%
“…At shallower depth of 1000 km (40 GPa), Liu et al . [ 5 ] found that H 2 O induced oxidation of ferropericlase to form Fe 2 O 3+δ with a new hexagonal structure. Both reactions result in further oxygen enrichment beyond the already highly oxidized slab materials in the deep mantle environment.…”
mentioning
confidence: 99%